The Effect of Pulsed Current and Organic Additives on Hydrogen Incorporation in Electroformed Copper Used in Ultrahigh Vacuum Applications. Issue 10 (1st January 2019) - Amador, L. Lain; Rolet, J.; Doche, M-L; Massuti-Ballester, P.; Gigandet, M-P; Moutarlier, V.; Taborelli, M.; Ferreira, L. M. A.; Chiggiato, P.; Hihn, J-Y
Abstract : The presence of hydrogen in electroformed copper from two different acidic copper sulfate solutions was evaluated: an additive-free solution and a solution including a sugar. D-xylose addition is found to inhibit H incorporation and allows the use of higher cathodic pulses before the copper diffusion limited range starts. TDS experiments show that hydrogen is trapped in the copper samples in two different forms. Hydrogen diffused from copper vacancies was found on all samples at an outgassing temperature of around 450°C. For samples with long pulse times, an additional H2 outgassing peak was found at around 600°C. XRD measurements allowed us to determine the preferential orientation of the plated samples and to monitor lattice parameter evolution with increasing temperature.